Lead in Painting Workers at Indonesia Land Transportation Manufacture Company - Benny Dwi Prasetyo; Endang Dwiyanti (Institute of Medico-legal Publications Pvt Ltd, 2021)
Lead is widely used in various industrial purposes, one of which is in the paint industry. Lead plays an important role in the paint industry which functions as a coloring agent or known as pigment. Lead is a heavy metal whose benefit is unknown in the body. In fact, its existence in the body often causes toxic effects on health. In painting activities, lead can more easily interact and poison paint workers through inhalation, ingestion, and skin. Accute lead poisoning can result in haematological disorders. This study aimed to reveal the level of lead in the air in the painting area and to analyze the differences in lead and hemoglobin levels. This observational study used an analytic cross-sectional design. The study population consisted of 2 groups, namely the study group (exposed group) and the control group (non-exposed group) as a comparison. The research subjects were 20 people consisting of 12 respondents from the exposed group and 8 respondents from the unexposed group.The results of this study indicate that the average exposure to lead levels in the air is0.06834 mg/m3. There was a difference between the lead levels of the exposed group and the unexposed group (sig: 0,00). And there was no difference between the hemoglobin levels of the both groups (sig: 0,349).